The Effect of the SSPBLS Model Using Quizizz Media on the Learning Outcomes of High School Students on Digestive System Materials - Nur Khasanah, Rahma; Kusumadani, Annur Indra; Mulyono, Yatin (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study aims to analyze the application of SSPBLS (Socio-Scientific Problem based Learning with Spiritual Value) on digestive system materials at SMA Muhammadiyah 1 Sragen for the academic year 2024/2025 and to find out whether this model can improve student learning outcomes. The type of research used is quantitative with experimental design. Data collection was carried out through learning outcome tests, observations, and interviews. Based on the results of the t-test, a significance value (sig.) of 0.22 was obtained, which was more than 0.05, which showed that there was no significant difference between the experimental group using the SSPBLS model and the control group using conventional learning methods. The results of this study show that the application of the SSPBLS model to the digestive system material in terms of final average scores can improve student learning outcomes. These results show that SSPBLS has the potential to improve student understanding through a problem-based approach that connects scientific phenomena with social issues, and its application in the field has met expectations. This research contributes to enriching contextual learning approaches through the application of the SSPBLS model which is proven to improve student learning outcomes by integrating social issues, critical thinking skills, and character values and provides alternative effective learning strategies to improve learning outcomes, with an emphasis on students' active involvement in solving problems based on social issues.